2014
DOI: 10.1128/microbiolspec.aid-0019-2014
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Antibodies

Abstract: Antibodies can impact pathogens in the presence or in the absence of effector cells or effector molecules such as complement, and experiments can often sort out with precision the mechanisms by which an antibody inhibits a pathogen in vitro. In addition, in vivo models, particularly those engineered to knock in or knock out effector cells or effector molecules, are excellent tools for understanding antibody functions. However, it is highly likely that multiple antibody functions occur simultaneously or sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(85 citation statements)
references
References 263 publications
(183 reference statements)
1
82
0
2
Order By: Relevance
“…1A). Previous studies showed that some antibodies inhibited infectivity by binding to viruses and causing them to aggregate (37). This could explain the additional efficiency displayed by the MAb 3A5 IgG in our study, for the Fab without the Fc fragment lost its virus-aggregating capability.…”
Section: Discussionsupporting
confidence: 53%
“…1A). Previous studies showed that some antibodies inhibited infectivity by binding to viruses and causing them to aggregate (37). This could explain the additional efficiency displayed by the MAb 3A5 IgG in our study, for the Fab without the Fc fragment lost its virus-aggregating capability.…”
Section: Discussionsupporting
confidence: 53%
“…Non-neutralizing monoclonal antibodies have demonstrated some success in mouse protection studies against other alphaviruses, including Sindbis virus [ 27 ], Semliki Forest virus [ 17 ] and VEEV [ 20 , 28 ]. The mechanism of action of ToR68-2C3 is undefined, but protection may be attributed to complement-mediated lysis or antibody-dependent cell-mediated lysis of infected cells [ 29 , 30 ]. Together, these data highlight the importance of in vivo evaluation of both neutralizing and non-neutralizing monoclonal antibodies for protective efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Both NHBA and NadA are involved in bacterial adherence, and neutralizing antibodies against either protein reduce the ability of Nm to adhere to epithelial cells (112, 113). Non-neutralizing antibodies provide protection against viruses (114, 115); however, similar data are scarce for bacteria (114). Targeting bacterial virulence factors or physiologically important proteins with a vaccine could discourage mutations that would allow the protein to evade immune detection, thereby improving the vaccine's success.…”
Section: Vaccine Decision Treementioning
confidence: 99%